Kuat Tekan Mortar Dengan Penambahan Pecahan Kaca - Rahayu, Ratna Dwi (SIMETRIS, 2024)
Mortar is a mixture of cement, sand and water. Mortar as an adhesive for masonry and plaster continues to increase in use. Sand is a limited natural resource. This research aims to determine the compressive strength of mortar that uses broken glass as an additional material to replace sand. The glass shards used are glass shards that pass through a sieve with a diameter of ≤ 0.5 cm. The mortar studied was in the form of a cube measuring 50 mm x 50 mm x 50 mm with a cement and sand volume ratio of 1: 4 and 10% water from the cement and sand mixture. Variations in the percentage of broken glass made are 5%, 10%, 15%, 20%. The test was carried out when the mortar was 7 days old using an ADR Touch 2000 Standard Compression Machine. The results of the research show that the more glass fragments are added, the compressive strength of the mortar decreases.